VD_FINDINFO HC / 2010 / 544 vom 21. Juni 2010 - VD Tribunal cantonal (2010)
OBLIGATION D'ENTRETIEN, PERSONNE DIVORCÉE, FORTUNE PRISE EN CONSIDÉRATION | 125 CC, 138 al. 1 CC, 163 CC, 451 ch. 2 CPC, 452 al. 2 CPC